Substrates for seedlings with sewage sludge and biochar - Becker Monteiro, Alex; dos Santos Pereira, Ivan; Bamberg, Adilson Luís; Mariliz Stöcker, Cristiane; Timm, Luís Carlos (Revista Ceres, 2025)
The objective of this study was to evaluate substrates formulated with proportions of sewage sludge (SS)-solarized and SS-biochar in the production of seedlings of two indicator crops: lettuce (Lactuca sativa L.) and black wattle (Acacia decurrens Willd). The study was composed of two experiments conducted in greenhouse, in randomized block designs. The treatments consisted of five doses of SS-solarized and SS-biochar, combined with rice husk ash and vermiculite in different proportions (20:40:40, 30:35:35, 40:30:30, 50:25:25 and 60:20:20) and two commercial substrates (controls). Morphophysiological characteristics of the seedlings and the physico-hydric characteristics, pH and electrical conductivity of the substrates were evaluated. The pyrolysis process enhanced the characteristics of SS as a component of substrates, where the substrate with 20% of SS-biochar, 40% of vermiculite and 40% of rice husk ash, presented the better performance.